2014
DOI: 10.1016/j.molimm.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of binding of PEGs and PEG-like oligomers to anti-PEG antibodies induced by methoxyPEG-proteins

Abstract: The use of methoxypoly(ethylene glycol) (mPEG) in PEG conjugates of proteins and non-protein therapeutic agents has led to the recognition that the polymer components of such conjugates can induce anti-PEG antibodies (anti-PEGs) that may accelerate the clearance and reduce the efficacy of the conjugates. Others have classified anti-PEGs as "methoxy-specific" or "backbone-specific". The results of our previous research on anti-PEGs in the sera of rabbits immunized with mPEG or hydroxyPEG (HO-PEG) conjugates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 17 publications
2
57
0
Order By: Relevance
“…The competition efficiency of the different PEG species on a molar basis increased with polymer length and with the presence of terminal methoxy groups. Saifer (40) recently tested the specificity of various monoclonal and polyclonal anti-PEG antibodies raised against PEG polymers with or without terminal methoxy groups. The authors demonstrated that antibodies against PEG polymers were never truly specific for methoxy PEGs or ethoxy PEGs, but recognized PEG polymers of different sizes with and without terminal Example of a subject who showed persistent positive results for anti-PEG IgG antibodies which were high enough in titer to be confirmed for specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The competition efficiency of the different PEG species on a molar basis increased with polymer length and with the presence of terminal methoxy groups. Saifer (40) recently tested the specificity of various monoclonal and polyclonal anti-PEG antibodies raised against PEG polymers with or without terminal methoxy groups. The authors demonstrated that antibodies against PEG polymers were never truly specific for methoxy PEGs or ethoxy PEGs, but recognized PEG polymers of different sizes with and without terminal Example of a subject who showed persistent positive results for anti-PEG IgG antibodies which were high enough in titer to be confirmed for specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-PEG-B-47 antibody recognizes PEG polymers of different lengths with and without terminal methoxy groups (40). Details of the monoclonal antibody and the study design are outlined in Online Supplement 3.…”
Section: Potential Cross-reactivity Of Anti-peg Antibodies With Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that an induced anti-PEG IgM will recognize only a PEG moiety. Recently, Sherman et al proposed a methodology to classify anti-PEG 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 antibodies into the following categories: "terminal methoxy-specific" or "backbone-specific" 21, 38 . They showed that methoxy-specific anti-PEG antibodies bind preferentially to methoxy-PEG rather than to the PEG diol, but backbone-specific anti-PEG antibodies show no apparent differences in the affinity for either methoxy-PEG or the PEG diol.…”
Section: Discussionmentioning
confidence: 99%
“…For this particular format, Casein in PBS from Thermo Fisher Scientific provided the lowest signal for the (14,15) previously reported on the detrimental effects of such surfactants on the sensitivity of detection for anti-PEG antibodies. Since our positive control antibody is PEG backbone unit specific, the interference was expected.…”
Section: Assay Buffermentioning
confidence: 99%